Analisis Pemahaman Landasan Pendidikan pada Mahasiswa Calon Guru dan Dampaknya terhadap Praktik Mengajar - Rahmah, Atika; Zelviana Az Zahro; Laila Rahma Nasution; Gusmaneli, Gusmaneli (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The foundations of education are fundamental aspects that prospective teachers must understand to equip them for their professional roles in education. Understanding the foundations of education encompasses philosophical, sociological, psychological, and legal dimensions, serving as a foundation for designing, implementing, and disseminating the learning process. However, in practice, various problems persist, such as theoretical understanding, a lack of connection between concepts and practice, and limited student reflective skills. This situation impacts the suboptimal quality of teaching practice. This article aims to examine the concept and scope of the foundations of education, identify issues in student teachers' understanding, and analyze their impact on prospective teachers' practice. Furthermore, the discussion focuses on strategies for strengthening understanding of the foundations of education through curriculum integration, the application of active learning methods, reflective activities, collaboration with partner schools, and the provision of relevant learning resources. By understanding the foundations of education systematically and contextually, prospective teachers are expected to develop balanced pedagogical, professional, and personal competencies, thus preparing them to face future educational challenges.